Parameter dependences of the separatrix density in nitrogen seeded ASDEX Upgrade H-mode discharges. (15th February 2018) - Kallenbach, A; Sun, H J; Eich, T; Carralero, D; Hobirk, J; Scarabosio, A; Siccinio, M
Abstract: The upstream separatrix electron density is an important interface parameter for core performance and divertor power exhaust. It has been measured in ASDEX Upgrade H-mode discharges by means of Thomson scattering using a self-consistent estimate of the upstream electron temperature under the assumption of Spitzer–Härm electron conduction. Its dependence on various plasma parameters has been tested for different plasma conditions in H-mode. The leading parameter determining n e, sep was found to be the neutral divertor pressure, which can be considered as an engineering parameter since it is determined mainly by the gas puff rate and the pumping speed. The experimentally found parameter dependence of n e, sep, which is dominated by the divertor neutral pressure, could be approximately reconciled by 2-point modelling.